Implementation tensions and challenges in donor funded curriculum projects: a case analysis of environmental and population education projects in Lesotho - Monaheng, Nkaiseng Ì•MamotÅ¡elisi (Rhodes University, Faculty of Education, Department of Education, 2007)
This study aims to capture the challenges and tensions that arise in donor funded curriculum projects in Lesotho. Through an interpretive case study research design I investigated these challenges and tensions in two projects relevant to Education for Sustainable Development, namely the Lesotho Environmental Support Project (LEESP) and the Population/Family Education (POP/FLE) projects which are donor funded curriculum projects funded by DANIDA and UNFPA respectively. A review of donor funded curriculum projects in the field of environmental education/Education for Sustainable Development was undertaken to provide background and a theoretical context for the study. It highlighted different challenges and implementation tensions experienced by other similar projects in other countries. At the heart of such projects lies a particular political economy, which is based on development assistance to poor countries. Such development assistance is constructed around concepts of need, participation and innovation, and donor-recipient relationships. It is structured around a system of governance and management that normally uses logical framework planning as its main methodology. This political economy has shaped the two donor funded projects that were considered in this study, and has shaped many of the tensions and challenges identified in the study. To investigate the two projects, data for this study was generated through in-depth interviews, document analysis and focus group interviews, with people who had been involved with the projects at the national level. The data generation process did not involve the schools where the projects were ultimately implemented, as it was seeking to identify how local institutions such as the National Curriculum Development Centre could support better synergies between donor funded initiatives and the local context. The findings of the study revealed the ambivalent nature of donor initiatives, and identified that the political economy and donor-recipient relations influence the projects. Aspects such as the design and management of projects, the processes associated with introducing innovation in educational ideas and paradigms, pedagogical issues, and staff contributions and ownership were identified as some of the key tensions that existed in the projects. Other factors such as poor capacity levels of local staff, non-alignment with existing structures, inadequate sustainability mechanisms and the difficulty of the envisaged integration of new paradigm thinking (methods and approaches) into the existing curriculum framework were also significant tensions, given the positivist history of the Lesotho curriculum. The study recommends the need to establish mechanisms for working with donors to tackle the tensions that arise in such projects within longer-term donor assistance. It proposes that government should expedite the development of policy on donor coordination. Both donors and the NCDC need to put mechanisms in place to allow for debate and discussions on innovations brought in by the donors in relation to local needs. The study further recommends that in cases where more than one donor exists, the NCDC and the donors should work towards developing synergies between the different initiatives to avoid duplication and overlap. Finally, there is a need for projects to use bottom-up approaches for the design and formulation of projects to ensure ownership.
Keywords: National Curriculum Development Centre (Lesotho); Curriculum planning -- Lesotho; Environmental education -- Lesotho; Economic assistance -- Lesotho; Technical assistance -- Lesotho; Sustainable development -- Lesotho